Fibrilacion Auricular por Via Accesoria - Puga, Marcelo Vicente; Navia Intriago, Otilia L.; Gómez Hernández, Aileen; Gómez Núñez, Katiuska (Revista Cubana de Cardiología y Cirugía Cardiovascular, 2018)
No corresponde